THE ROLE OF DISTANCE LEARNING IN ENGLISH - Urakova Zarifa Rustam qizi; Abbosova Muqaddas Baxtiyorovna (TADQIQOTLAR.UZ, 2024)
This article delves into the expanding importance of distance learning within the realm of English language education, exploring its definition concerning language acquisition and proficiency while highlighting its relevance in today's technology- driven era. The text emphasizes the critical role of distance learning in nurturing English language skills, particularly in response to the growing demand and the worldwide shift towards remote education. Through assessing the impacts and potential obstacles of distance learning, the goal is to offer valuable perspectives for educators, policymakers, and learners to maximize the benefits of distance learning in advancing English language proficiency.